Consumo de refrigerante, frutose dietética e ácido úrico sérico : resultados da linha de base do Estudo Longitudinal de Saúde do Adulto (ELSA-Brasil) - Siqueira, Jordana Herzog (2017)
The secular trend of hyperuricemia coincides with an important increase in the consumption of sugar-sweetened beverages. The aim of this study was to identify the consumption of sugar-sweetened soft drinks, dietary fructose and unsweetened, nonprocessed fruit juices, as well evaluate the association between the consumption of these beverages and total dietary fructose and serum uric acid in Brazilian adults. We performed a cross-sectional analysis of baseline data from the Brazilian Longitudinal Study of Adult Health - ELSA-Brasil. Of the 15,105 participants (35-74 years old) at baseline, data were analysed from 7,173 (both sexes), after excluding those who reported taking medications for gout, hypertension and diabetes, previous bariatric surgery, implausible caloric consumption, extremes of body mass index and those who reported consuming diet soft drinks. The explanatory variables were the consumption of soft drinks, fruit juice and fructose. Information on dietary intake was estimated using a validated semi-quantitative food frequency questionnaire. The outcomes were hyperuricemia (uric acid >7.0 mg/dL in men and >6.0 mg/dL in women) and the uric acid concentration in serum. Regression models were tested, and a significance level of 5% was adopted. It was observed that the consumption of soft drinks is higher in men and decreases with age, as observed for the consumption of fruit juice. Also the consumption of dietary fructose is higher in men and increases with age. In men, after adjustment for confounding variables, daily consumption of a portion of soft drink (250 mL) almost doubled the chance of occurrence of hyperuricemia (OR = 1.89; CI95% 1.39-2.57). In women, the consumption of ≥0.1 to <1.0 soft drink/day was associated with a higher chance of hyperuricemia (OR = 1.61, CI95% 1.18-2.18). In men, high fructose consumption (OR = 1.30, CI95% 1.00-1.68) and, in women, the moderate (OR = 1.48, CI95% 1.03-2.14) and high consumption (OR = 1.47, CI95% 1.00- 2.20) were associated with hyperuricemia. All categories of soft drinks consumption were linearly associated with increased serum uric acid, but the consumption of fruit juice was not statistically associated with serum uric acid and hyperuricemia. Our findings suggest that the consumption of soft drinks and dietary fructose is positively associated with a higher chance of hyperuricemia and high levels of uric acid in adults.